2012
DOI: 10.1590/s1806-37132012000100010
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniae: sensibilidade a penicilina e moxifloxacina

Abstract: Objective: To determine the minimum inhibitory concentrations (MICs) of parenteral penicillin and moxifloxacin against Streptococcus pneumoniae strains isolated at a hospital center. Methods: In-vitro, prospective study involving 100 S. pneumoniae isolates collected from patients who had been treated, between October of 2008 and July of 2010, at the Hospital das Clínicas complex of the University of São Paulo School of Medicine, located in the city of São Paulo, Brazil. The isolates were obtained from respirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The prevalence of penicillin resistance seems to be variable, with reported rates as low as 0% [53] , [54] , [55] and as high as 27.9% [25] , [54] in Brazil. It is important to point out that previously published rates used the 2008 CLSI breakpoints to determine β-lactams susceptibility, and in this study, penicillin MICs ≥4 µg/mL were not observed.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of penicillin resistance seems to be variable, with reported rates as low as 0% [53] , [54] , [55] and as high as 27.9% [25] , [54] in Brazil. It is important to point out that previously published rates used the 2008 CLSI breakpoints to determine β-lactams susceptibility, and in this study, penicillin MICs ≥4 µg/mL were not observed.…”
Section: Discussionmentioning
confidence: 99%
“…3 This communication then describes what appears as a previously unreported picture of pneumococcal pathology, and is the first to include pneumococci within the spectrum of wound infecting pathogens. 4…”
mentioning
confidence: 99%
“…S pneumoniae resistance to antibiotics has spread all over the world. 1,4 Penicillin-resistant strains structurally modify PBPs (penicillin-binding proteins). 4 Macrolide-resistant isolates express an ermB - or mefA -related 23S methylase (conferring resistance to 14-, 15-, and 16-membered-ring macrolides, lincosamides, and streptogramin B [MLS B phenotype]) or efflux pumps (extruding 14- and 15-membered-ring macrolides only).…”
mentioning
confidence: 99%
See 2 more Smart Citations